Delayed‐onset Friedreich's ataxia revisited. Issue 1 (21st September 2015) - Lecocq, Claire; Charles, Perrine; Azulay, Jean‐Philippe; Meissner, Wassilios; Rai, Myriam; N'Guyen, Karine; Péréon, Yann; Fabre, Nelly; Robin, Elsa; Courtois, Sylvie; Guyant‐Maréchal, Lucie; Zagnoli, Fabien; et al.
ABSTRACT: Background: Friedreich's ataxia usually occurs before the age of 25. Rare variants have been described, such as late‐onset Friedreich's ataxia and very‐late‐onset Friedreich's ataxia, occurring after 25 and 40 years, respectively. We describe the clinical, functional, and molecular findings from a large series of late‐onset Friedreich's ataxia and very‐late‐onset Friedreich's ataxia and compare them with typical‐onset Friedreich's ataxia. Methods: Phenotypic and genotypic comparison of 44 late‐onset Friedreich's ataxia, 30 very late‐onset Friedreich's ataxia, and 180 typical Friedreich's ataxia was undertaken. Results: Delayed‐onset Friedreich's ataxia (late‐onset Friedreich's ataxia and very‐late‐onset Friedreich's ataxia) had less frequently dysarthria, abolished tendon reflexes, extensor plantar reflexes, weakness, amyotrophy, ganglionopathy, cerebellar atrophy, scoliosis, and cardiomyopathy than typical‐onset Friedreich's ataxia, along with less severe functional disability and shorter GAA expansion on the smaller allele ( P < 0.001). Delayed‐onset Friedreich's ataxia had lower scale for the assessment and rating of ataxia and spinocerebellar degeneration functional scores and longer disease duration before wheelchair confinement ( P < 0.001). Both GAA expansions were negatively correlated to age at disease onset ( P < 0.001), but the smaller GAA expansion accounted for 62.9% of age at onset variation and the larger GAA expansion for 15.6%. In this comparative study of late‐onset Friedreich's ataxia and very‐late‐onset Friedreich's ataxia, no differences between these phenotypes were demonstrated. Conclusion: Typical‐ and delayed‐onset Friedreich's ataxia are different and Friedreich's ataxia is heterogeneous. Late‐onset Friedreich's ataxia and very‐late‐onset Friedreich's ataxia appear to belong to the same clinical and molecular continuum and should be considered together as "delayed‐onset Friedreich's ataxia." As the most frequently inherited ataxia, Friedreich's ataxia should be considered facing compatible pictures, including atypical phenotypes (spastic ataxia, retained reflexes, lack of dysarthria, and lack of extraneurological signs), delayed disease onset (even after 60 years of age), and/or slow disease progression.